Unsur-unsur Zoomorfik dalam Seni Rupa Islam - Amri Yahya (Al-Jami'ah Research Centre, 2000)
On the one hand, the appearance of visual factors in the Islamic fine arts which projects an image of pictures about creatures or forms of animal (zoomorphic), can possibly be related to the Islamic concept and spiritualization in valuing and regarding God's creatures as noble. This can also be confined to the various forms of aesthetic expressions which rise and grow in cultural history at the local environment. On the other hand, visualization of fine arts expressions cannot totally be liberated from the Islamic law perspective (fiqhiyyah) which states that drawing picture of living creatures can be categorized as forbidden acts. Therefore, various aspects of creativity and expression as well as theory and practice of fine arts in contemporary lslamic culture become neglected and marginalized from religious discourses.